Analyzing the Impact of Corporate Governance in Enhancing Firms’ Financial Performance and Sustainability - Saeed, Mohamed Nasr; Rahmouni, Mohieddine; Haroun, Mohammed Adam; Hassan, Eid Awad; Elfaki, Ibrahim Omer; Tayfor, Abdelsamie Eltayeb; Abbas, Amani Mohammed (Journal of Posthumanism, 2025)
This study aims to critically examine existing governance frameworks, assess their impact on financial performance, and explore executive perspectives on governance practices within the agricultural, food, and petrochemical sectors. Employing a mixed-methods approach, the research combines quantitative surveys and qualitative interviews, focusing on (45) companies listed on the Saudi Stock Exchange. Statistical methods include descriptive statistics, correlation analysis, and multiple regression to analyze the data. Key findings reveal a statistically significant positive relationship between governance compliance and financial performance indicators like Return on Assets (ROA) and Dividends per Share (DPS), indicating that higher governance compliance leads to improved asset efficiency and dividend payouts. However, no significant links were found between governance compliance and liquidity or debt structure. The research highlights the importance of corporate governance in enhancing accountability, resource allocation, and strategic decision-making, contributing to financial outcomes. Recommendations for policymakers suggest a reassessment of existing governance mechanisms and further reforms to enhance practices, while stakeholders are encouraged to promote compliance to drive performance and sustainability. This study contributes to the literature by providing empirical evidence of the governance-performance relationship in an emerging market context, emphasizing the significance of governance practices in driving sustainability and financial performance in sectors vital for diversification of the dynamic Saudi economy.